Evolutionary and biogeographical implications of degraded LAGLIDADG endonuclease functionality and group I intron occurrence in stony corals (Scleractinia) and mushroom corals (Corallimorpharia) - Palazzo, Alexander F.; Celis, Juan Sebastián; Edgell, David R.; Stelbrink, Björn; Wibberg, Daniel; Hauffe, Torsten; Blom, Jochen; Kalinowski, Jörn; Wilke, Thomas; Justus Liebig University Giessen (My University, 2017)
Group I introns and homing endonuclease genes (HEGs) are mobile genetic elements, capable of invading target sequences in intron-less genomes. LAGLIDADG HEGs are the largest family of endonucleases, playing a key role in the mobility of group I introns in a process known as homing . Group I introns and HEGs are rare in metazoans, and can be mainly found inserted in the COXI gene of some sponges and cnidarians, including stony corals (Scleractinia) and mushroom corals (Corallimorpharia). Vertical and horizontal intron transfer mechanisms have been proposed as explanations for intron occurrence in cnidarians. However, the central role of LAGLIDADG motifs in intron mobility mechanisms remains poorly understood. To resolve questions regarding the evolutionary origin and distribution of group I introns and HEGs in Scleractinia and Corallimorpharia, we examined intron/HEGs sequences within a comprehensive phylogenetic framework. Analyses of LAGLIDADG motif conservation showed a high degree of degradation in complex Scleractinia and Corallimorpharia. Moreover, the two motifs lack the respective acidic residues necessary for metal-ion binding and catalysis, potentially impairing horizontal intron mobility. In contrast, both motifs are highly conserved within robust Scleractinia, indicating a fully functional endonuclease capable of promoting horizontal intron transference. A higher rate of non-synonymous substitutions (Ka) detected in the HEGs of complex Scleractinia and Corallimorpharia suggests degradation of the HEG, whereas lower Ka rates in robust Scleractinia are consistent with a scenario of purifying selection. Molecular-clock analyses and ancestral inference of intron type indicated an earlier intron insertion in complex Scleractinia and Corallimorpharia in comparison to robust Scleractinia. These findings suggest that the lack of horizontal intron transfers in the former two groups is related to an age-dependent degradation of the endonuclease activity. Moreover, they also explain the peculiar geographical patterns of introns in stony and mushroom corals.
Keywords: ddc:570